LITERATURE REVIEW: INQUIRY-BASED LEARNING ON SCIENTIFIC ATTITUDES IN SCIENCE LEARNING IN SECONDARY EDUCATION - Iswanto, Imas Hari; Suryani, Dewi; Jannah, Miftahul (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
Inquiry-based learning is a learning model in which students create meaningful and useful knowledge by asking questions, exploring, and analyzing information based on their existing knowledge. This study aims to determine the impact of inquiry-based learning on scientific attitudes and which inquiry learning models are commonly used in secondary school science education. This study is a qualitative research project that uses a systematic literature review method. The analysis of the systematic literature review revealed that implementing inquiry-based learning positively impacts students' scientific attitudes in science learning, including biology, physics, and chemistry, in secondary education. The most common type of inquiry learning model used is guided inquiry.